Botulinum toxin improves pain in chronic anal fissure. Issue 6 (November 2017) - Amorim, Hugo; Santoalha, José; Cadilha, Rui; Festas, Maria‐José; Barbosa, Paula; Gomes, Armanda
ABSTRACT : Highlights : Chronic anal fissure is a common condition associated with intense pain. Local botulinum toxin injection is a valid option in its management. Pain intensity scores significantly improved after BoNT injection. Side effects were rare and mild. Our results support the inclusion of BoNT in the management algorithm of chronic anal fissure. Introduction: : Chronic anal fissure is a common condition associated with intense pain. Local botulinum toxin injection is a valid option in its management. The purpose of this study was to evaluate the efficacy of botulinum toxin on pain relief in chronic anal fissure patients. Methods: : We conducted a retrospective cohort study, involving 81 consecutive patients referred to a chronic pain management unit due to a chronic anal fissure for treatment with botulinum toxin, during a 4 year period. Data were collected from hospital records regarding pre‐treatment and post‐treatment pain (numeric rating scale), side effects, need for botulinum toxin reinjection and need for surgical treatment. We used standard statistical methods for inter ( t ‐test and qui 2 ) and intra‐group (paired sample t ‐test) comparisons, according to variables distribution. Results: : Pain intensity rest score significantly improved after BoNT injection [variation: −4.2 ± 2.9 ( p < 0.001)], as did pain post‐defecation score [variation: −5.1 ± 3.0 ( p < 0.001)]. 8.6% needed botulinum toxin reinjection and 23.5% were submitted to surgery. Side effects were reported in 8.6%. Discussion: : The efficacy of botulinum toxin use on pain reduction along with its non‐permanent and minor side effects support its role in the resolution of chronic anal fissure. However, treatment failure in the long term is still significant. Conclusion: : Botulinum toxin is effective on pain relief in patients with chronic anal fissure, which supports its inclusion in the management algorithm of this condition.